Efektivitas Media Kartu Flashcard, Leaflet, Video terhadap Pengetahuan dan Sikap Isi Piringku pada Anak SD - Indrawiananda Nur Sandrina; Ratih Kurniasari (PPNI UNIMMAN, 2025)
Meeting the nutritional needs of school-age children is an important factor in supporting their health and academic achievement, especially for school children who spend most of their time at school. One form of education about balanced nutrition introduced by the Indonesian government is the Isi Piringku (Fill My Plate) program. This program serves as a dietary guide that emphasizes balanced food consumption in each serving. The main objective of this study was to understand the extent of the influence of educational media such as leaflets, audiovisual videos, and games, considering the use of flashcards in conveying the concept of balanced nutrition and encouraging healthy eating behavior changes in children. Through this approach, the study sought to identify the most effective media so that it could be used as a model for nutrition education in elementary schools. The results of this study found that there was a significant increase in knowledge between the pretest and posttest conducted on the three media (p < 0.05), while a significant change in attitude only occurred in the Leaflet and Video media (p < 0.05). The Kruskal-Wallis test also showed that there was no significant difference between the three educational media (p > 0.05).